Impact of Unconventional Monetary Policies of Advanced Economies on Emerging Asian Economies - Peddada, Kameswari (Indian Journal of Finance, 2017)
After the global financial crisis of 2007, advanced economies have been following unique but divergent monetary policies to come out of the subsequent recession. They tried stimulus packages, quantitative easing policies, and drastic cuts in lending rates to kick-start their moribund economies. Some European economies and Japan have adopted ultra low and even negative interest rate policies to stimulate liquidity in markets, investment in businesses, consumption, employment, and economic growth. Even the USA and the UK, outside the European Union, have drastically slashed their interest rates and are assessing the situation. Some emerging market economies too are toying with such ideas, if found workable. Some unconventional monetary policies adopted were unheard of till recently. Their cost-effectiveness, sustainability, and repercussions are yet to be fully assessed. It is important to study their implications for advanced economies and the debilitating spillover in emerging Asian economies, the ways and means to cope with them, and the safeguards to sustain growth and stability in such a backdrop. An extensive study of relevant literature was undertaken in this paper to learn more about such policies and their likely repercussions and come out with suitable findings, conclusions, and suggestions, in general, for the emerging economies of Asia.